Poziom specyficznych koordynacyjnych zdolnosci motorycznych (KZM) i wybranych elementów techniki gry pilkarek rêcznych trenujacych i po zakonczeniu kariery - roznice i wspolzaleznosci - Diaczuk, J.; Pawelak, Z. (Human Movement, 2001)
The aim of research The evaluation of CMA (co-ordination motor abilities) in female handball players at different sports levels. The determination of relationships between CMA and chosen technical skills in female players of different sports levels. Material and methods Female players from the sports school in Gliwice participating in cadets junior level and former, retired players from the 1st division. For the evaluation of co-ordination abilities specific tests were applied, each for different abilities. Technical skills were evaluated by a self-constructed test. Results The evaluation of the level of co-ordination abilities did not show significant increases with age and sports level. Only the level of kinaesthetic differentiation and the ability to adjust increased significantly with age and training experience. The level of technical skills shows a high relationship with training experience. Conclusions There is no statistical significance among groups of juniors according to the co-ordinational motor abilities levels, except for the spatial orientational ability (p <= 0,01). The correlation between the specific co-ordinational motor abilities level and technical level of performance in handball players has not been found.